Pogge’s account of global poverty and responses from elementary teachers - Pacaol, Niñoval F. (Penerbit Universiti Kebangsaan Malaysia, 2020)
It is the overriding objective of international organizations and some intellectuals to provide practical ways in solving the issue of global poverty. From a philosophical reading towards a qualitative design, this paper aims to answer the question of obligation among affluent countries and its people for the eradication of worldwide poverty as posed by some moral and political theorists. The research hinges on the guide and approach of Thomas Pogge’s account of Global Poverty. Then, using the descriptive method, the paper bridges the gap of a global issue to the fringes of local perspectives as it affects education and knowledge-production. Elementary teachers served as the participants of the study to gather responses concerning global perspectives on the issue. The following themes reflect the teachers’ responses: 1) prevalence of inequalities, 2) socioeconomic gain from discriminatory advantage, 3) creation of social problems, 4) quality of living as indication of progress, and 5) ‘we are in the same world’.